2019
DOI: 10.1108/pr-11-2017-0348
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mediating role of job embeddedness: evidence of Iranian context

Abstract: Purpose The purpose of this paper is to investigate the mediating role of job embeddedness in the relationship between perceived job security and perceived job flexibility and its impact on creative performance. Design/methodology/approach The statistical population of this study consisted of all employees at the Electricity Company of Mashhad, and a sample comprising 300 participants was finalized. In order to analyze the data, different statistical analysis methods were used, including Pearson’s correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 52 publications
0
30
0
1
Order By: Relevance
“…Based on above discussion, it is pertinent to study deeply about JE characteristics in turnover theory. Limited studies (Rahimnia et al, 2019) have been found related to turnover intention that particularly emphasis on the different dimensions of JE on VTOI that enhance the organizational support in the form of better embeddedness, a long with the role of CWP. Therefore, it is pertinent to have deep routes of JE characteristics to extend the turnover theory in education sector, where creative role performance in the form of teaching and research in important.…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 99%
See 3 more Smart Citations
“…Based on above discussion, it is pertinent to study deeply about JE characteristics in turnover theory. Limited studies (Rahimnia et al, 2019) have been found related to turnover intention that particularly emphasis on the different dimensions of JE on VTOI that enhance the organizational support in the form of better embeddedness, a long with the role of CWP. Therefore, it is pertinent to have deep routes of JE characteristics to extend the turnover theory in education sector, where creative role performance in the form of teaching and research in important.…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 99%
“…CWP can be explained as the capability to generate new solutions for effectually solving problems and the behavioral propensity of individuals to be imaginative at the workplace. It can be linked with the performance of academics when they can create new ideas for teaching and research (Rahimnia et al, 2019). High CWP at the workplace is related with higher on-the-job or off-the-job organizational support.…”
Section: Job Embeddedness (Je) and Voluntary Turnover Intention (Vtoi)mentioning
confidence: 99%
See 2 more Smart Citations
“…The limited literature on JE status has resulted in the necessity of reviewing the basic understanding of JE theory and its implications (Alqarni, 2016). Within the foci of current JE theory, a high perceived job security by organizational-and community-embeddedness practices has been found to reduce the propensity to find alternative jobs (Karatepe & Vatankhah, 2014;Rahimnia et al, 2019). Therefore, regarding the continued attention on organizational initiatives to enhance embeddedness within the private and public sectors, a precise understanding of the relationship between JE and TOI is required to address the challenging nature of JE practices (Karatepe & Vatankhah, 2014).…”
Section: Introductionmentioning
confidence: 99%